Degradable DOX-loaded zinc-doped molybdenum disulfide nano-composite material capable of inhibiting tumor drug resistance as well as preparation and application of DOX-loaded zinc-doped molybdenum disulfide nano-composite material
By loading the chemotherapy drug DOX in zinc-doped molybdenum disulfide nanocomposite and rapidly decreasing and distributing drugs under the tumor microenvironment, the problem of insignificant acoustic dynamics and chemotherapy resistance in the treatment of triple-negative breast cancer is solved, and the problem of insignificant acoustic dynamics and chemotherapy resistance in the treatment of triple-negative breast cancer is achieved. Synergistic sound dynamics therapy, chemotherapy and gas treatment effects.
Patent Information
- Application Number
- CN202411499663.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-07
AI Technical Summary
The prior art has problems in the treatment of triple-negative breast cancer, such as insignificant acoustic dynamics, cancer cells are resistant to chemotherapy drugs, and are not easy to metabolize and excrete, which leads to long-term toxicity.
Using zinc-doped molybdenum disulfide nanocomposites that can inhibit tumor resistance and degradability, can improve the acoustic dynamics of the sound-sensitive agent through ion doping and forming heterojunctions, and quickly decrease and interpret the release under the tumor microenvironment. DOX and Zn2+ are used to synergistically achieve acoustic dynamic therapy, chemotherapy and gas therapy.
It enhances the effect of acoustic dynamics therapy, overcomes the resistance of chemotherapy drugs, reduces the long-term toxicity of nanocomposites, and enhances the effect of chemotherapy by improving the tumor hypoxic environment.
Smart Images

Figure CN119386201A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanocomposite particles, and in particular to a degradable zinc-doped molybdenum disulfide nanocomposite material capable of inhibiting tumor drug resistance and loaded with DOX, and the preparation and application thereof. Background Art
[0002] Triple-negative breast cancer (TNBC) is difficult to diagnose in the early stage and is highly invasive, making it one of the leading causes of death among women worldwide. Currently, the main treatments for triple-negative breast cancer are surgery, radiotherapy (RT), chemotherapy, and endocrine therapy. However, these treatments cannot specifically treat tumors and have significant toxic side effects. Therefore, it is necessary to develop specific tumor treatments for the treatment of TNBC. In recent years, sonodynamic therapy (SDT) has attracted much attention due to its high temporal and spatial selectivity, high penetration depth, and excellent biosafety. Inorganic nanosonosensitizers have been widely used in tumor SDT due to their unique performance advantages. Compared with organic nanosonosensitizers, inorganic nanosonosensitizers have rich physicochemical properties and better chemical and mechanical stability. However, the effect of a single SDT is limited, so researchers combine different tumor treatments with SDT to enhance the tumor treatment effect, such as chemotherapy, chemodynamic therapy (CDT), starvation therapy, gas therapy (GT), immunotherapy, etc. Although synergistic SDT treatment has made rapid progress, some challenges still exist: the sonodynamic effect of sonosensitizers is not significant and the therapeutic effect is poor; cancer cells develop resistance to chemotherapy drugs, which greatly weakens the effect of chemotherapy; sonosensitizers are not easily metabolized and cleared, resulting in long-term toxicity, etc.
[0003] Patent publication number CN118453892A discloses a molybdenum disulfide drug delivery system and its preparation method and application. The above drug delivery system uses MoS2 nanoparticles as the basic skeleton structure, and MnO2 is coated on its surface to form a mesoporous core-shell structure, loads the anti-tumor chemotherapy drug DOX, and finally PEG is modified on the surface of MnO2. Its effective ingredients are: MoS260%-65%, MnO222-30%, DOX10%-13%, PEG5%-10%. It has the advantages of tumor microenvironment response, good water solubility, good stability and high DOX loading rate, and can enhance the therapeutic effect of tumors by combining photothermal and chemotherapy. However, the patented drug cannot alleviate tumor hypoxia; it cannot alleviate tumor resistance from the root, and cannot be applied to tumor cells resistant to chemotherapy drugs; the therapeutic effect is single, only photothermal and chemotherapy are combined, and the penetration depth is limited, and photothermal therapy is difficult to treat deep tumors; it is difficult to degrade and remove, and it is easy to produce long-term toxicity. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the above-mentioned prior art, such as the insignificant sonodynamic effect, the resistance of cancer cells to the chemotherapy drug doxorubicin (DOX), and the difficulty in metabolizing and excreting to produce long-term toxicity, and to provide a degradable zinc-doped molybdenum disulfide nanocomposite loaded with DOX that can inhibit tumor resistance and its preparation and application, which can respond to the tumor microenvironment, rapidly degrade and clear, and be used for the treatment of TNBC, and improve the sonodynamic effect of the sonosensitizer by ion doping and forming a heterojunction. In addition, the zinc-doped molybdenum disulfide nanocomposite loaded with DOX is used to simultaneously achieve the synergistic treatment of sonodynamic therapy, chemotherapy and gas therapy for triple-negative breast cancer.
[0005] Combining chemotherapy, gas therapy and sonodynamic therapy can synergistically enhance the therapeutic effect of tumors.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] One of the technical solutions of the present invention is to provide a degradable zinc-doped molybdenum disulfide nanomaterial that can inhibit tumor drug resistance, characterized in that the zinc-doped molybdenum disulfide nanomaterial is a two-dimensional nanosheet structure, with a sheet-like MoS2 nanomaterial as the main body, and the sheet-like MoS2 nanomaterial is uniformly doped with Zn ions. The zinc-doped molybdenum disulfide nanomaterial is a Zn-MoS2 nanomaterial, that is, a ZMS nanomaterial.
[0008] Furthermore, the mass ratio of the flaky MoS2 nanomaterial to the Zn element is 1 to 10:1.
[0009] Furthermore, the average particle size of the zinc-doped molybdenum disulfide nanomaterial is 130-170 nm.
[0010] The second technical solution of the present invention is to provide a method for preparing a degradable zinc-doped molybdenum disulfide nanomaterial that can inhibit tumor resistance. Sodium oleate, sodium molybdate tetrahydrate, thiourea and zinc nitrate hexahydrate are dissolved in a solvent, stirred until uniform, and the pH is adjusted and then stirred until the solution is clear, and a hydrothermal reaction is carried out. After the reaction is completed, the product is collected, washed, dried, and crushed to obtain a ZMS nanomaterial, that is, the target product zinc-doped molybdenum disulfide nanomaterial.
[0011] Furthermore, the solvent is a mixed solution of ionized water, ethanol and oleic acid, and the volume ratio thereof is 5-20:5-20:1-10;
[0012] The mass volume ratio of the sodium oleate, sodium molybdate tetrahydrate, thiourea, zinc nitrate hexahydrate and the solvent is (1-15) g: (1-10) g: (1-15) g: (1-5) g: 100 mL, preferably (4.5-5.5) g: (3-4) g: (5.5-6) g: (0.25-0.3) g: 100 mL.
[0013] Further, sodium oleate, sodium molybdate tetrahydrate, thiourea and zinc nitrate hexahydrate are dissolved in a solvent, stirred until uniform, and the pH after adjusting the pH is 0.5 to 3, preferably 1 to 2.
[0014] Furthermore, dilute hydrochloric acid is used to adjust the pH, and the concentration of the dilute hydrochloric acid is 1.5-2.5M.
[0015] Furthermore, the temperature of the hydrothermal reaction is 175-185° C., and the time is 20-30 hours.
[0016] Furthermore, after the reaction is completed, the product is collected by centrifugation.
[0017] Furthermore, the centrifugal speed is 9000-10000 rpm, and the centrifugal time is 10-20 min.
[0018] Furthermore, the cleaning was performed with deionized water and ethanol for 3 times.
[0019] Furthermore, the drying temperature is 50-70° C. and the drying time is 12-24 hours.
[0020] Furthermore, the crushing power is 550-650W, and the time is 5-10h.
[0021] The third technical solution of the present invention is to provide a zinc-doped molybdenum disulfide nanocomposite material loaded with DOX that can inhibit tumor resistance and is degradable, comprising the zinc-doped molybdenum disulfide nanomaterial and the anticancer drug DOX. The zinc-doped molybdenum disulfide nanomaterial is an anticancer drug release carrier, and the anticancer drug DOX is loaded on the zinc-doped molybdenum disulfide nanomaterial.
[0022] The fourth technical solution of the present invention is to provide a method for preparing a zinc-doped molybdenum disulfide nanocomposite material loaded with DOX that can inhibit tumor resistance and is degradable, wherein the zinc-doped molybdenum disulfide nanomaterial is mixed with the anticancer drug DOX, stirred, centrifuged and washed under light-proof conditions to obtain a ZMS / DOX nanocomposite material, that is, the target product, a zinc-doped molybdenum disulfide nanocomposite material loaded with DOX.
[0023] The fifth technical solution of the present invention is to provide an application of a degradable zinc-doped molybdenum disulfide nanocomposite material loaded with DOX that can inhibit tumor drug resistance, characterized in that the zinc-doped molybdenum disulfide nanocomposite material loaded with DOX is used to prepare anti-tumor drugs.
[0024] Furthermore, the tumor includes triple-negative breast cancer and its drug-resistant strains.
[0025] Furthermore, in the weakly acidic environment of the tumor, the H2O2 environment and the ultrasonic environment, the zinc-doped molybdenum disulfide nanocomposite loaded with DOX is used to simultaneously achieve the synergistic treatment of triple-negative breast cancer by sonodynamic therapy, chemotherapy and gas therapy. The zinc-doped molybdenum disulfide nanocomposite loaded with DOX can itself be used as a sonodynamic therapy drug, the H2S released by it can be used as gas therapy, and the loaded DOX can be used as chemotherapy, so the zinc-doped molybdenum disulfide nanocomposite loaded with DOX can simultaneously achieve these three therapies, enhance sonodynamic therapy, overcome chemotherapy drug resistance, and be used to release H2S for gas therapy. Currently, most of them are single therapies, or only combine two therapies.
[0026] The ZMS / DOX nanocomposite material introduces S defects due to Zn doping, and the band gap of ZMS is significantly narrowed, making ZMS more easily activated by exogenous US; in addition, S defects act as electron traps to inhibit the activation of e - -h + The ZMS nanosheets release Zn 2+ and H2S. Zn 2+ The release of MoS2 reduces the production of intracellular ATP by interfering with the glycolysis of cancer cells, and H2S gas therapy synergistically reduces the intracellular ATP content by damaging the mitochondrial electron transport chain. The reduction of ATP can inhibit the P-glycoprotein (P-gp) of drug-resistant tumors and overcome the resistance of chemotherapy drugs. In addition, the catalase-like activity of MoS2 converts H2O2 in TME into O2, alleviating the hypoxic environment of the tumor. The synergistic treatment of drug-resistant triple-negative breast cancer with sonodynamic therapy, chemotherapy and gas therapy is achieved.
[0027] In the present invention, ZMS nanomaterials (i.e., Zn-doped MoS2 nanosheets) were synthesized by a one-pot method, and the two-dimensional structure of MoS2 was used to load the chemotherapy drug DOX to obtain a ZMS / DOX nanocomposite material for SDT-enhanced chemotherapy and GT synergistic treatment of drug-resistant TNBC. Zn doping causes sulfur defects in MoS2, reduces the band gap width, and promotes electron-hole (e-hole) - -h + ) separation, enhancing the SDT effect. 2+ The release of H2S can synergistically damage mitochondrial function, reduce the production of ATP in tumor cells, inhibit the expression of P-gp and the drug efflux caused by it. At the same time, the catalase-like performance of MoS2 can convert H2O2 in TME into O2, improve the hypoxic environment of tumors, and enhance the effect of chemotherapy. The constructed ZMS / DOX nanocomposite material realizes the synergistic treatment of drug-resistant TNBC with SDT, GT, and chemotherapy.
[0028] Compared with the prior art, the present invention has the following advantages:
[0029] (1) The ZMS / DOX nanocomposite material prepared by the present invention has a stable structure and a small particle size.
[0030] (2) Since the Zn doping introduces S defects into the ZMS nanomaterial prepared by the present invention, the band gap of ZMS is significantly narrowed, making ZMS more easily activated by exogenous US and enhancing the generation of reactive oxygen species after ultrasound.
[0031] (3) The ZMS nanomaterial prepared in the present invention has an adsorption effect and effectively delivers DOX to tumor tissue.
[0032] (4) The ZMS / DOX nanocomposite prepared by the present invention has a triple sensitive degradation effect under the weak acid environment of tumor, H2O2 environment and ultrasonic irradiation, and can effectively release DOX and Zn after degradation. 2+ . Zn 2+ The release of DOX reduces the production of intracellular ATP by interfering with the glycolysis of cancer cells, and synergistically inhibits the expression of P-gp together with the generated ROS, thereby inhibiting tumor resistance and enhancing the chemotherapeutic effect of DOX.
[0033] (5) The MoS2 in the degradable DOX-loaded molybdenum disulfide nanocomposite material prepared by the present invention that can inhibit tumor drug resistance reacts with H2O2 to generate O2, which can improve the hypoxia of the tumor microenvironment (TME) to enhance SDT.
[0034] (6) The degradable DOX-loaded molybdenum disulfide nanocomposite material prepared by the present invention, which can inhibit tumor drug resistance, produces H2S which can also damage mitochondria under weakly acidic conditions, and performs gas therapy. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a transmission electron microscope image of the ZMS nanomaterial in Example 1 of the present invention;
[0036] Figure 2 Element mapping diagram of the ZMS nanomaterial in Example 1 of the present invention;
[0037] Figure 3 This is a particle size distribution diagram of the ZMS nanomaterial in Example 1 of the present invention;
[0038] Figure 4 It is the ultraviolet absorption graph of ZMS, DOX and ZMS / DOX in Example 1 of the present invention;
[0039] Figure 5 : Zeta potential diagram of ZMS, DOX and ZMS / DOX in Example 1 of the present invention;
[0040] Figure 6 is a vacancy map of the ZMS nanomaterial in Example 1 of the present invention;
[0041] Figure 7 This is the O2 release diagram of the ZMS nanomaterial in Example 1 of the present invention;
[0042] Figure 8 This is a graph of H2S release of the ZMS nanomaterial at different pH values in Example 1 of the present invention;
[0043] Fig. 9 This is a graph showing the cell viability of the ZMS nanomaterial in Example 1 of the present invention;
[0044] Fig.10 The ZMS nanomaterial in Example 1 of the present invention is Zn under different conditions. 2+ Release curve diagram;
[0045] Fig.11 Transmission electron micrographs of the degradation experiment of the ZMS nanomaterial in Example 1 of the present invention, (a) ZMS not degraded, (b) ZMS incubated with pH 7.4 for 48 hours, (c) ZMS incubated with pH 6.5 for 48 hours, (d) ZMS incubated with pH 6.5+H2O2 for 48 hours;
[0046] Fig.12 This is a ROS detection diagram of the ZMS nanomaterial in Example 1 of the present invention;
[0047] Fig.13 This is a DOX release curve of the ZMS / DOX nanocomposite material under different conditions in Example 1 of the present invention;
[0048] Fig.14 This is a graph of the cellular ATP content of the ZMS nanomaterial in Example 1 of the present invention;
[0049] Fig.15 This is the WB protein expression diagram of the ZMS / DOX nanocomposite material in Example 1 of the present invention;
[0050] Fig.16 Figure 2 is a graph showing the change in mouse tumor volume of the ZMS / DOX nanocomposite material in Example 1 of the present invention, (a) relative tumor volume, and (b) mouse tumor photograph. DETAILED DESCRIPTION
[0051] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments. Based on the given embodiments, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0052] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art.
[0053] In the following examples, the purity of DOX was 98%, the purity of MB was AR70%, both of which were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., and the PBS was prepared by itself, PBS7.4=14.505gNa2HPO4·12H2O+1.482gNaH2PO4·2H2O+250mL H2O, PBS6.5=5.641gNa2HPO4·12H2O+5.343g NaH2PO4·2H2O+250mLH2O, PBS5.6=0.882g citric acid monohydrate+4.647g sodium citrate dihydrate+100mL H2O; L929 cells are C3H / An mouse connective tissue cells purchased from the Chinese Academy of Sciences Cell Bank, MDA-MB-231 / ADR cells are human breast cancer cells resistant to adriamycin, purchased from Shanghai Lianzu Biotechnology Co., Ltd.; the model of PVDF membrane is SD0043, and the brand of phosphatase and protease inhibitor combination is SD0001, both purchased from Shanghai Siding Biotechnology Co., Ltd.; the model of nude mice is BALB / c nude, hairless and thymusless, purchased from Shanghai Experimental Animal Center. The brand of WSP-1 fluorescent probe is C3614, purchased from APExBIO, USA, and the brand of Immobilon Western HRP substrate is WBKLS0050, purchased from Merck Millipore.
[0054] Example 1
[0055] This embodiment provides a ZMS, a ZMS / DOX nanocomposite material for tumor treatment and a preparation method thereof, wherein the preparation method comprises the following steps:
[0056] (1) Preparation of ZMS nanosheets
[0057] 1.6g sodium oleate, 1.17g sodium molybdate tetrahydrate, 1.85g thiourea, 0.0875g zinc nitrate hexahydrate were dissolved in 15mL deionized water, 15mL ethanol and 2mL oleic acid mixed solution, and magnetic stirring was used to mix evenly. The pH value of the mixture was adjusted to 1 with 2M hydrochloric acid, and magnetic stirring was continued until the solution was clear. The mixture was placed in a 50mL polytetrafluoroethylene liner and hydrothermally reacted at 180°C for 24h. Naturally cooled to room temperature, centrifuged at 10000rpm for 15min to collect the product. Washed with deionized water and anhydrous ethanol 3 times, and placed in a 60°C oven for drying for 24h. The product obtained by the above method was crushed with an ultrasonic cell crusher at a power of 600W for 6h to obtain ZMS nanosheets with a particle size of about 150nm, i.e., ZMS nanomaterials.
[0058] (2) Preparation of ZMS / DOX nanocomposites
[0059] 10 mg of the prepared ZMS nanomaterial was mixed with 10 mg of DOX (i.e., doxorubicin) solution, stirred at room temperature for 24 h under light-proof conditions, centrifuged at 10,000 rpm for 15 min, and washed with deionized water to obtain ZMS / DOX nanosheets, i.e., ZMS / DOX nanocomposite materials.
[0060] Comparative Example 1
[0061] Compared with Example 1, most of the steps are the same except that zinc nitrate hexahydrate is omitted.
[0062] Dissolve 1.6g sodium oleate, 1.17g sodium molybdate tetrahydrate, and 1.85g thiourea in a mixed solution of 15mL deionized water, 15mL ethanol, and 2mL oleic acid, and stir magnetically until the mixture is evenly mixed. Adjust the pH value of the mixture to 1 with 2M hydrochloric acid, continue magnetic stirring until the solution is clear, put the mixture into a 50mL polytetrafluoroethylene liner, and hydrothermally react at 180°C for 24h. Cool naturally to room temperature, and collect the product by centrifugation at 10000rpm for 15min. Wash with deionized water and anhydrous ethanol 3 times, and put it in a 60°C oven for drying for 24h. The product obtained by the above method was crushed for 6h at a power of 600W using an ultrasonic cell crusher to obtain MoS2.
[0063] The performance of the ZMS nanomaterial and the ZMS / DOX nanocomposite material prepared in Example 1 was tested.
[0064] 1. Microstructure of Nanosheets and Successful Loading of DOX
[0065] like Figure 1 As shown in Figure 2, the prepared ZMS nanosheets have a distinct sheet structure and are evenly dispersed. The element distribution image shows that Zn, Mo, and S elements are all present in the nanosheets, indicating the successful incorporation of Zn ( Figure 2). Dynamic light scattering proves that the size of ZMS nanomaterials is around 150nm ( Figure 3 ), which means that the ZMS nanomaterials were successfully prepared and have uniform size. Figure 4 As shown in Figure 2, after loading with DOX, the ZMS nanosheets showed a characteristic peak of DOX at 485 nm, indicating the successful loading of DOX. The potential of ZMS increased significantly after loading with DOX ( Figure 5 ), which also proves the successful loading of DOX. Figure 6 As shown, the ZMS nanosheets synthesized in Example 1 have more vacancies than the MoS2 in Comparative Example 1, which proves that the sonodynamic therapy effect of ZMS is better.
[0066] 2. Detection of O2 generation of ZMS nanosheets
[0067] The ZMS nanosheets (1 mg / mL) and H2O2 (1 mL, 100 mM) obtained in Example 1 were placed in a 50 mL centrifuge tube and stirred magnetically. The dissolved oxygen production of the ZMS nanosheets within 10 min was measured using a dissolved oxygen meter. At the same time, H2O2 (1 mL, 100 mM) without ZMS nanosheets was set as a control group. The results are shown in Figure 2. Figure 7 As shown, ZMS nanosheets gradually produced dissolved oxygen in the presence of H2O2. In contrast, the control group produced no O2, indicating that ZMS nanosheets can improve the hypoxic environment of tumors.
[0068] 3. Detection of H2S generation of ZMS nanosheets
[0069] The Washington State Probe-1 (WSP-1) fluorescent probe was used to quantitatively measure the H2S release of the ZMS nanosheets obtained in Example 1. 50 μL of 200 μg / mL ZMS nanosheets obtained in Example 1 at different pH values were mixed with 50 μL of WSP-1 fluorescent probe and incubated in a shaker at 37°C and 200 rpm for 1 h in the dark. The fluorescence intensity of WSP-1 was then measured using an ELISA reader (Ex = 465 nm, Em = 515 nm). The results are shown in Table 1. Figure 8 As shown, the H2S released by ZMS increased with decreasing pH, indicating that ZMS specifically released a large amount of H2S in the TME.
[0070] 4. Cell viability test of ZMS nanosheets
[0071] The CCK-8 method was used to evaluate the cytotoxicity of ZMS nanosheets. L929 cells (Cell Bank of the Chinese Academy of Sciences) and MDA-MB-231 / ADR cells (Shanghai Lianzu Biotechnology Co., Ltd.) were inoculated into 96-well plates (1×104 / well) and placed in an incubator for incubation for 24 hours. The cells were then incubated with different concentrations (0, 12.5, 25, 50, 100, 200 μg / mL) of ZMS obtained in Example 1 for 24 hours. After discarding the supernatant, the cells were washed with PBS buffer solution, and the original culture medium was replaced with 100 μL of culture medium containing 10% CCK. The culture was continued for 1 hour, and the OD value of each well was detected by an enzyme reader (detection wavelength 490 nm). The results are as follows. Fig. 9 As shown, when the concentration of ZMS nanosheets reached 200 μg / mL, the cell viability of L929 and MDA-MB-231 / ADR was still higher than 90%, indicating that ZMS nanosheets exhibited excellent biocompatibility in normal cells.
[0072] 5. Zn of ZMS nanosheets 2+ Unleash performance
[0073] 1.6 mg of ZMS nanosheets obtained in Example 1 were added to 8 mL of PBS buffer solutions of pH 7.4, pH 6.5, and pH 6.5+H2O2 (the concentration of H2O2 was 100 nM), and incubated in a shaker at 37°C and 200 rpm. The supernatant was collected at different time periods and supplemented with the same volume of fresh solution. The Zn content was determined by inductively coupled plasma spectroscopy (ICP-OES). 2+ The amount of release.
[0074] The results are as follows Fig.10 As shown, at pH 7.4, Zn 2+ The release is slow, which indicates that ZMS is stable in normal tissues; at pH 6.5, Zn 2+ The release is accelerated. In the environment of pH 6.5 + H2O2, ZMS reacts with H2O2 and undergoes rapid cleavage. 2+ The release of Zn was significantly enhanced, indicating that ZMS can quickly release Zn under TME. 2+ , laying the foundation for collaborative treatment.
[0075] 6. Degradation performance of ZMS nanosheets
[0076] The ZMS obtained in Example 1 was dispersed in three groups of PBS buffer solutions, Group 1: H2O2 = 0, pH = 6.5, ZMS = 1 mg / mL; Group 2: H2O2 = 0, pH = 7.4, ZMS = 1 mg / mL; Group 3: H2O2 = 100 mM, pH = 6.5, ZMS = 1 mg / mL. The solutions were shaken and stirred at 37°C and 200 rpm for 48 hours. The degradation behavior of ZMS was evaluated by transmission electron microscopy. The results are shown in Figure 2. Fig.11 As shown, ZMS gradually broke down at pH = 6.5, and under the combined action of pH = 6.5 + H2O2, ZMS was more significantly degraded, indicating that ZMS can be doubly degraded under the tumor environment and US.
[0077] 7. Determination of reactive oxygen species (ROS) in ZMS nanosheets under ultrasound
[0078] Control group: 1 mL deionized water + MB (2 mL, 10 μg / mL);
[0079] US group: 1 mL deionized water + MB (2 mL, 10 μg / mL) + US (1.0 W / cm 2 , 1MHz, 50% duty cycle);
[0080] MoS2 group: 1mL 600μg / mL MoS2+MB (2mL, 10μg / mL);
[0081] MoS2+US group: 1mL 600μg / mL MoS2+MB(2mL,10μg / mL)+US(1.0W / cm 2 , 1MHz, 50% duty cycle);
[0082] ZMS group: 1mL 600μg / mL ZMS+MB (2mL, 10μg / mL);
[0083] ZMS+US group: 1mL 600μg / mL ZMS+MB(2mL,10μg / mL)+US(1.0W / cm 2 , 1MHz, 50% duty cycle).
[0084] ZMS (1 mL, 600 μg / mL) obtained in Example 1 and methylene blue (MB) (2 mL, 10 μg / mL) were mixed. The decreasing trend of MB absorbance at 650 nm after and without ultrasonic treatment was detected by UV spectrophotometer. The results are as follows: Fig.12As shown in the figure, almost no ROS was generated in the Control group and the US group, and the ROS generation in the synthesized ZMS nanosheet group was much stronger than that in the MoS2 group, which proved that the sonodynamic therapy effect of the ZMS nanosheet was better. The attenuation trend of the MoS2+US group was weaker than that of the ZMS+US group, and the attenuation trend of the ZMS+US group was the strongest among all the groups. The characteristic peak of MB at around 650nm decreased significantly with the increase of US time, indicating the gradual generation of ·OH under the action of US.
[0085] 8. Testing the drug release of ZMS / DOX nanosheets
[0086] Four groups of ZMS / DOX nanosheets under different conditions were set up for drug release tests.
[0087] Group 1 (pH 6.5): 1.2 mg of the ZMS / DOX nanosheets obtained in Example 1 was added to 5 mL of PBS buffer solution with a pH value of 6.5, and placed in a shaker at 37° C. away from light.
[0088] Group 2 (pH 7.4): 1.2 mg of the ZMS / DOX nanosheets obtained in Example 1 were added to 5 mL of PBS buffer solution with a pH value of 7.4, and placed in a shaker at 37° C. away from light.
[0089] Group 3 (pH 6.5+H2O2): 1.2 mg of the ZMS / DOX nanosheets obtained in Example 1 was added to 5 mL of PBS buffer solution with a pH value of 6.5 and a H2O2 concentration of 100 mM, and placed in a shaker at 37°C away from light.
[0090] Group 4 (pH 6.5 + H2O2 + US): 1.2 mg of the ZMS / DOX nanosheets obtained in Example 1 were added to 5 mL of PBS buffer solution with a pH value of 6.5 and a H2O2 concentration of 100 mM, and ultrasonicated using a 120 W ultrasonic cleaner.
[0091] The drug release results of the four groups of ZMS / DOX nanosheets are shown in Fig.13 As shown, at pH = 7.4, the percentage of DOX released by ZMS / DOX nanosheets is about 25%. In a weakly acidic environment at pH = 6.5, the release amount is greater than that at pH = 7.4. The release amount is further increased after adding H2O2. Finally, the percentage of DOX released by ZMS / DOX nanosheets under pH 6.5 + H2O2 + US irradiation is the largest, which can reach about 55%, indicating that ZMS / DOX nanocomposites can release the maximum amount of chemotherapy drugs DOX under the dual stimulation of tumor environment and US irradiation.
[0092] 9. Detection of cellular ATP content in ZMS nanosheets
[0093] The intracellular ATP content was detected using an ATP detection kit. MDA-MB-231 / ADR cells were cultured at 1×10 4 The cells were inoculated into 96-well plates at a density of 100 / well and cultured in an incubator for 24 hours. They were divided into the following 4 groups: Control, US, ZMS, and ZMS+US.
[0094] Group 1 (Control): No operation;
[0095] Group 2 (US): 1W / cm 2 ,1MHz,50% duty cycle,3 minutes;
[0096] Group 3 (ZMS): 200 μg / mL ZMS;
[0097] Group 4 (ZMS+US): 200 μg / mL ZMS+US (1 W / cm 2 ,1MHz,50% duty cycle,3 minutes).
[0098] The ZMS obtained in Example 1 was added to the well plate and incubated for 6 hours and treated with different conditions. The cell supernatant was collected and the cells were further digested, and the cell suspension was collected. Then, 20 μL of the supernatant was collected by centrifugation and added to 100 μL of ATP detection working solution to measure the chemiluminescence value of the cells. The results are shown in Fig.14 As shown in Figure 2, ZMS releases H2S and Zn due to the weakly acidic and H2O2-rich environment of tumor cells. 2+ , Zn 2+ The release of Zn2S reduces the production of intracellular ATP by interfering with the glycolysis of cancer cells. H2S gas treatment reduces the intracellular ATP content by damaging the mitochondrial electron transport chain. Therefore, the ATP content of the ZMS group decreased significantly. Since the ZMS+US group can produce a large amount of ROS, which causes mitochondrial oxidative stress and reduces ATP production, the ATP content of the ZMS+US group decreased further. This indicates that excessive H2S, Zn2S and Zn3S can reduce the production of ATP. 2+ Together with ROS, it inhibits the production of ATP.
[0099] 10. Cellular WB protein expression of ZMS / DOX nanosheets
[0100] Immunoblotting was used to detect the content of P-gp in drug-resistant cells under different conditions. MDA-MB231 / ADR cells were seeded into 6-well plates at a density of 2×106 cells / well and incubated in an incubator for 24 hours to allow them to adhere to the wall. They were divided into the following four groups: Control, DOX, ZMS / DOX, and ZMS / DOX+US.
[0101] Group 1 (Control): No operation;
[0102] Group 2 (US): 1W / cm 2 ,1MHz,10% duty cycle,2 minutes;
[0103] Group 3 (ZMS): 10 μg / mL ZMS;
[0104] Group 4 (ZMS+US): 10 μg / mL ZMS+US (1 W / cm 2 ,1MHz,10% duty cycle,2 minutes).
[0105] The cells were collected, washed with pre-cooled PBS, and then lysed with RIPA buffer (1% deoxycholate, 1% Triton X-100, 0.1% SDS plus phosphatase inhibitors and protease inhibitors), and shaken repeatedly to allow the reagent to fully contact the cells. The lysate was treated with SDS PAGE and then transferred to a PVDF membrane (Shanghai Siding Biotechnology Co., Ltd.), and the PVDF membrane was blocked with skim milk for 2 hours at room temperature. After the primary antibody was gently shaken at 4°C overnight, the secondary antibody continued to act for 2 hours. After incubation with Immobilon Western HRP substrate (Millipore, WBKLS0050), protein expression was detected using the ChemiScope 6000 Touch integrated chemiluminescence imaging system (Clinx, Shanghai). The results are shown in Fig.15 As shown in the figure, after DOX treatment, the P-gp content of cells did not change significantly, the P-gp in the ZMS / DOX group was significantly reduced, and the Pgp content in the ZMS / DOX+US group was the lowest, indicating that the expression of P-gp was significantly inhibited under the synergistic effect of US and ZMS.
[0106] 11. Changes in mouse tumor volume with ZMS / DOX nanosheets
[0107] MDA-MB-231 / ARD cells were injected subcutaneously into the axillary region of healthy nude mice (Shanghai Experimental Animal Center). 3 MDA-MB-231 / ARD tumor-bearing mice were obtained. MDA-MB-231 / ARD tumor-bearing mice were divided into five groups (n=3 in each group): (1) control group, (2) US, (3) DOX, (4) ZMS / DOX, and (5) ZMS / DOX+US. The concentration of ZMS / DOX was 400 μg / mL, and the concentration of ZMS in the ZMS group and the concentration of DOX in the DOX group were consistent with those in the ZMS / DOX group. Mice in the US group and the ZMS / DOX+US group were subjected to US (1.0 MHz, 50% duty cycle 1.0 W / cm 2The weight of mice during the 10-day treatment period was recorded, and the tumor size was measured with a vernier caliper to calculate the tumor volume (mm 3 ), the formula is as follows: tumor volume (mm 3 )=(length×width 2 ) / 2. On the 10th day of treatment, the mice were killed, the tumors were removed, and photos were taken for preservation. Fig.16 As shown, in the DOX group, tumor growth was not inhibited, indicating that the tumor was resistant to DOX treatment. In contrast, in the ZMS / DOX group, tumor volume was slightly reduced, indicating that drug resistance was partially reversed under the action of ZMS. It is worth noting that in the ZMS / DOX+US group, the tumor was significantly reduced, which was due to the excellent synergistic therapeutic effect of ROS generated by ZMS under the action of US and ZMS.
[0108] Although the present invention has been described in detail above by means of general description, specific implementation methods and tests, it is obvious to those skilled in the art that some modifications or improvements may be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A degradable zinc-doped molybdenum disulfide nanomaterial capable of inhibiting tumor drug resistance, characterized in that: The zinc-doped molybdenum disulfide nanomaterial is a two-dimensional nanosheet structure, with flaky MoS2 nanomaterial as the main body, and Zn ions are uniformly doped inside the flaky MoS2 nanomaterial.
2. The degradable zinc-doped molybdenum disulfide nanomaterial capable of inhibiting tumor drug resistance according to claim 1, characterized in that: The mass ratio of the Mo element to the doped Zn element in the flaky MoS2 nanomaterial is 1 to 10:
1.
3. The degradable zinc-doped molybdenum disulfide nanomaterial capable of inhibiting tumor drug resistance according to claim 1 or 2, characterized in that: The average particle size of the zinc-doped molybdenum disulfide nanomaterial is 130-170 nm.
4. The method for preparing a degradable zinc-doped molybdenum disulfide nanomaterial capable of inhibiting tumor drug resistance according to any one of claims 1 to 3, characterized in that: Sodium oleate, sodium molybdate tetrahydrate, thiourea and zinc nitrate hexahydrate are dissolved in a solvent, stirred until uniform, and the pH is adjusted and then stirred until the solution is clear, and a hydrothermal reaction is carried out. After the reaction is completed, the product is collected, washed, dried, and crushed to obtain ZMS nanomaterials, i.e., the target product zinc-doped molybdenum disulfide nanomaterials.
5. The method for preparing a degradable zinc-doped molybdenum disulfide nanomaterial capable of inhibiting tumor drug resistance according to claim 4, characterized in that: The solvent is a mixed solution of ionized water, ethanol and oleic acid, and the volume ratio thereof is 5-20:5-20:1-10; The mass volume ratio of the sodium oleate, sodium molybdate tetrahydrate, thiourea, zinc nitrate hexahydrate and the solvent is (1-15) g: (1-10) g: (1-15) g: (1-5) g: 100 mL.
6. The degradable zinc-doped molybdenum disulfide nanomaterial capable of inhibiting tumor drug resistance according to claim 4, characterized in that: Sodium oleate, sodium molybdate tetrahydrate, thiourea and zinc nitrate hexahydrate are dissolved in a solvent, stirred until uniform, and the pH after adjustment is 0.5-4.
7. The degradable zinc-doped molybdenum disulfide nanomaterial capable of inhibiting tumor drug resistance according to claim 4, characterized in that: The temperature of the hydrothermal reaction is 170-190°C.
8. A degradable zinc-doped molybdenum disulfide nanocomposite material capable of inhibiting tumor drug resistance, characterized in that: The invention comprises the zinc-doped molybdenum disulfide nanomaterial as described in any one of claims 1 to 3, and also comprises the anticancer drug DOX. The zinc-doped molybdenum disulfide nanomaterial is a release carrier of the anticancer drug, and the anticancer drug DOX is loaded on the zinc-doped molybdenum disulfide nanomaterial.
9. The method for preparing a degradable zinc-doped molybdenum disulfide nanocomposite material capable of inhibiting tumor drug resistance as claimed in claim 8, characterized in that: The zinc-doped molybdenum disulfide nanomaterial is mixed with the anticancer drug DOX, stirred, centrifuged and washed under light-proof conditions to obtain a ZMS / DOX nanocomposite material, that is, a target product, a zinc-doped molybdenum disulfide nanocomposite material loaded with DOX.
10. The use of a degradable zinc-doped molybdenum disulfide nanocomposite material capable of inhibiting tumor drug resistance as claimed in claim 8, characterized in that: The DOX-loaded zinc-doped molybdenum disulfide nanocomposite material is used for preparing anti-tumor drugs.
Citation Information
Patent Citations
Preparation and application of anti-tumor composite material based on molybdenum disulfide nanosheets
CN118453892A